The Use of Computer Graphics in Interactive Media Design, a Research - Tang, Qianyu (Transactions on Computer Science and Intelligent Systems Research, 2024)
In order to better meet user needs, user-oriented interactive design introduces computer graphics technology to generate, process, and transmit graphical information more effectively, thereby enhancing the practicality, simplicity, convenience, and enjoyment of interactive media. This paper aims to discuss the application of computer graphics in interactive media design. In order to analyze and compare the use of different computer graphics (CG) technologies in different scenarios, this paper classifies the interactive media into three categories according to the different focuses of the purposes, namely distributed interaction media, commercial interaction media and informational interaction media, and discusses the application of computer graphics in interactive media design with specific examples. This paper analyzes and compares the use of different CG technologies in interactive media according to their different purposes, namely distributed interaction media, commercial interaction media and informational interaction media. The paper concludes with a summary of the current applications of computer graphics in interactive media design, and an outlook on the future use of CG technology in interactive media design.